Six widespread bacterial clones among Escherichia coli K1 isolates. - Achtman, M (1983)
Variable properties among Escherichia coli isolates include serotype, electrophoretic migration of major outer membrane proteins, metabolic properties, production of hemolysin or colicin or both, and plasmid content. These characteristics were compared in E. coli strains of capsular types K1, K5, K92, and K100 and in non-encapsulated isolates. The 234 bacterial strains from the United States and Europe which we studied had been isolated from healthy or diseased individuals recently or as long ago as 1941. Regardless of source, most O7:K1, O16:K1, and O75:K100 isolates could be assigned to three unique, serotype-specific groups, which were interpreted as representing three bacterial clones. Two bacterial (sub)clones each were discerned among the O18:K1 and O18:K5 isolates, and two further, distinct clones were discerned among the O1:K1 isolates. The implications of these results for epidemiological analyses and for virulence are discussed.